2021
DOI: 10.1111/den.13928
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde cholangiopancreatography and endoscopic ultrasound in children

Abstract: Gastrointestinal endoscopy is fundamental to diagnostic and therapeutic procedures in pediatric gastroenterology. In the decades since endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS) for hepatobiliary and pancreatic disease were introduced into clinical practice, there has been increasing interest in these procedures, and practice guidelines and position papers that clearly define the role of ERCP and EUS in children have been published. Based on the distinction of endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Hence, it is necessary to not only ensure the stability of patients' respiratory circulation but also achieve a satisfactory anesthetic effect during ERCP, which requires sedation, analgesia, no body movement, and security. The use of intraoperative neuroleptics and analgesics can significantly improve patients' discomfort and reduce the incidence of intraoperative adverse reactions and postoperative complications [ 28 ]. However, there are still some disadvantages to the sedation schemes used in clinical practice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to not only ensure the stability of patients' respiratory circulation but also achieve a satisfactory anesthetic effect during ERCP, which requires sedation, analgesia, no body movement, and security. The use of intraoperative neuroleptics and analgesics can significantly improve patients' discomfort and reduce the incidence of intraoperative adverse reactions and postoperative complications [ 28 ]. However, there are still some disadvantages to the sedation schemes used in clinical practice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent indication for EUS in our study was the investigation of the pancreaticobiliary tract (69% of our cases), which was similar to the existing literature. 13 In a recent study from the United States about the use of EUS in pediatric age group, the most common indications were pancreatic-related disorders such as pancreatic fluid collections (18.4%), recurrent chronic and acute pancreatitis (14.3%), and acute pancreatitis characterization (13.3%). 14 …”
Section: Discussionmentioning
confidence: 99%
“…The most frequent indication for EUS in our study was the investigation of the pancreaticobiliary tract (69% of our cases), which was similar to the existing literature. 13 In a recent study from the United States about the use of EUS in pediatric age group, the most common indications were pancreatic-related disorders such as pancreatic fluid collections (18.4%), recurrent chronic and acute pancreatitis (14.3%), and acute pancreatitis characterization (13.3%). 14 While EUS was beneficial in the diagnosis of seven patients with chronic pancreatitis, three patients with pancreatic NET, two with resolving pseudocyst, one biliary rhabdomyosarcoma, it has also a valuable role in excluding suspected chronic pancreatitis in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread application of digestive endoscopy in children, adverse events (AEs) such as myoclonus, abdominal pain, fever, bleeding, chest pain, sore throat, vomiting, anosensation, esophageal reflux or ulcer, rash, delayed capsule discharge, perforation, pancreaticobile duct infection, and pancreatitis have occurred in children after digestive endoscopy (9,10). Statistical results indicated that the AEs after painless gastroenteroscopy reached 26.98% incidence (11).…”
Section: Original Articlementioning
confidence: 99%